Beneath the bite: A rare intramuscular lipoma - Karikal, Arvind; Pandya, Rutvi; Das, Subhajit (Indian Journal of Case Reports, 2025)
Lipomas are known to affect the head-and-neck region, but the involvement of muscle leading to the formation of intramuscular variant is rare and that too in masseter muscle is not reported except of 1 or 2 cases. This case report is of a young male patient aged 24 years which remains one of the very few cases reported for intramuscular lipoma in masseter muscle where the treatment comprised excision of the lesion along with a part of masseter muscle adhered to it under general anesthesia. Histopathological examination confirmed the finding, and the patient was followed up for 3 years postoperatively which had no signs of recurrence.